Становлення та розвиток медико-фармацевтичної школи в НТУ "ХПІ" - Пономарьов, Володимир Іванович; Грубник, Ігор Михайлович; Юдіна, Юлія Вікторівна (Національний технічний університет "Харківський політехнічний інститут", 2024)
Надано історичні передумови формування окремої медико-фармацевтичної школи в Національному технічному університеті (НТУ) «Харківський політехнічний інститут» (ХПІ), започаткування фармацевтичної та медичної освіти та найбільш вагомі й значущі здобутки наших науковців для медицини та фармації. Було надано історичні аспекти розвитку фармацевтичної та медичної школи на базі НТУ «ХПІ» з описом вчених, які внесли значний вклад в розвиток вітчизняної медичної та фармацевтичної школи. В історичному аспекті визначено значні досягнення вчених, які формували вітчизняну школу медицини та фармації в НТУ «ХПІ». Надано сучасний етап відродження медичної та фармацевтичної школи в НТУ «ХПІ», який було започатковано доктором медичних наук, професором Федаком Богданом Степановичем і доктором медичних наук, професором Пономарьовим Володимиром Івановичем, які під керівництвом ректора НТУ «ХПІ», члена-кореспондента Національної академії наук України (НАН), лауреата премії ім. С. О. Лебедєва НАН України, доктора технічних наук, професора Сокола Євгена Івановича сформували Навчально-науковий медичний інститут (ННМІ) при НТУ «ХПІ», який готує спеціалістів у галузі післядипломної освіти.

The article provides historical prerequisites for the formation of a separate medical and pharmaceutical school at the National Technical University (NTU) «Kharkiv Polytechnic Institute» (KhPI), the initiation of pharmaceutical and medical education, and the most important and significant achievements of our scientists for medicine and pharmacy. It was determined that the Kharkiv Institute of Technology was founded as a practical technological institute, and from the very beginning of its existence, a whole galaxy of outstanding scientists worked in it, who made a significant contribution to the development of pharmaceutical and medical science. Historical aspects of the development of the pharmaceutical and medical school on the basis of NTU «KhPI» were provided with a description of the scientists who made a significant contribution to the development of the domestic medical and pharmaceutical school. In the historical aspect, the significant achievements of the scientists who formed the national school of medicine and pharmacy at NTU «KhPI» are defined. Presented is the modern stage of the revival of the medical and pharmaceutical school at KhPI NTU, which was initiated by Doctor of Medical Sciences, Professor Fedak Bohdan Stepanovich and Doctor of Medical Sciences, Professor Volodymyr Ivanovich Ponomaryov, who under the leadership of the rector of NTU «KhPI», a corresponding member of the National Academy of Sciences of Ukraine, laureate of the award named after S. O. Lebedev of the National Academy of Sciences of Ukraine, Doctor of Technical Sciences, Professor Sokol Yevhen Ivanovych formed the Educational and Scientific Medical Institute at NTU «KhPI», which trains specialists in the field of postgraduate education.
Formation and development of the school of medicine and pharmacy at NTU "KhPI"
Keywords: медико-фармацевтична школа; Національний технічний університет "Харківський політехнічний інститут"; НТУ "ХПІ"; Навчально-науковий медичний інститут; вища освіта; Федак Богдан Степанович; medical and pharmaceutical school; National Technical University "Kharkiv Polytechnic Institute"; Fedak Bohdan Stepanovich